1984
DOI: 10.1002/art.1780270310
|View full text |Cite
|
Sign up to set email alerts
|

Neutral proteases capable of proteoglycan digesting activity in osteoarthritic and normal human articular cartilage

Abstract: Proteases have been postulated to account for the progressive disappearance of matrix proteoglycans in osteoarthritic (OA) cartilage. The digestion of endogenous proteoglycans by neutral proteases in human OA cartilage homogenates has been measured and compared with that of normal age-matched controls. Cartilage was obtained from 16 patients at the time of knee arthroplasty and from 7 accident victims. Tissue blocks were cut from the tibia1 plateau; part was used for histologic grading of the severity of OA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
55
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 155 publications
(59 citation statements)
references
References 34 publications
4
55
0
Order By: Relevance
“…However, immunofluorescence methods of analysis detect a few areas of type 1 collagen surrounding the clones or brood capsules Ehrlich et a1 (3) have demonstrated that osteoarthritic cartilage, in tissue cultures, produces increased amounts of collagenase. Using a direct tissue assay, we have demonstrated a positive correlation between the histologic severity of human osteoarthritic lesions and their levels of metalloproteases acting on collagen and on proteoglycan (1,2). In the dog model, we have shown that collagenolytic activity in cartilage is elevated at the time when early osteoarthritic changes are detected (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, immunofluorescence methods of analysis detect a few areas of type 1 collagen surrounding the clones or brood capsules Ehrlich et a1 (3) have demonstrated that osteoarthritic cartilage, in tissue cultures, produces increased amounts of collagenase. Using a direct tissue assay, we have demonstrated a positive correlation between the histologic severity of human osteoarthritic lesions and their levels of metalloproteases acting on collagen and on proteoglycan (1,2). In the dog model, we have shown that collagenolytic activity in cartilage is elevated at the time when early osteoarthritic changes are detected (6).…”
Section: Discussionmentioning
confidence: 99%
“…Collagenase, collagenolytic enzymes, and neutral proteoglycanase activity have been found to be increased in human osteoarthritic cartilage (1-4). The levels of these enzymes have been directly correlated with the severity of the disease (1,2). Using the Pond-Nuki dog model of osteoarthritis (3, we have recently shown a correlation between the collagenolytic enzyme activity and the early breakdown of the cartilage collagen network (6).…”
mentioning
confidence: 99%
“…This enzyme can be trypsin solubilized from rat livef plasma membranes without loss of activity (3 1). Enzymatic solubilization from chondrocytes in vivo by chondrocyte-derived neutral proteases, which are elevated in degenerated cartilage (32), is possible. Synovium and plasma must also be considered possible sources.…”
Section: Discussionmentioning
confidence: 99%
“…Mankin et a1 (5) The elevation of neutral proteinase has been demonstrated in human osteoarthritic articular cartilage (10). The enzyme was found at relatively uniform levels throughout the cartilage (not just in erosions), and the levels were correlated with disease severity as assessed histologically.…”
mentioning
confidence: 98%